Do controlling shareholders' expropriation incentives imply a link between corporate governance and firm value? Theory and evidence - Bae, Kee-Hong (2013)
We develop and test a model that investigates how controlling shareholders' expropriation incentives affect firm values during crisis and subsequent recovery periods. Consistent with the prediction of our model, we find that, during the 1997 Asian financial crisis, Asian firms with weaker corporate governance experience a larger drop in their share values but, during the post-crisis recovery period, such firms experience a larger rebound in their share values. We also find consistent evidence for Latin American firms during the 2001 Argentine economic crisis. Our results support the view that controlling shareholders' expropriation incentives imply a link between corporate governance and firm value.